The Voice and Person of the Prophet in Joel (and the Twelve) - Toffelmire, Colin M. (2022)
In this article, I argue that the presentation of the prophetic voice as belonging to an authoritative prophetic figure is an integral feature of the various books within the Twelve Minor Prophets and creates a situational context that simultaneously ties the prophetic book to an authority in the past and allows for the possibility of continued reuse of the prophetic books. By speaking with the prophetic voice, later readers and rereaders are able to take on, in some way, the mantle of the prophetic figure, as the text is reappropriated in new situations and times.